An improved global zonation method for geotechnical parameters - Qi, Xiaohui (2019)
Spatial prediction or interpolation of geotechnical parameters is a vital step in the designs or reliability analyses of geotechnical structures. Existing studies involving spatial predictions of geotechnical parameters ignore the distinction of spatial variabilities in zones along a horizontal direction, such as zones along a subway line. This study proposes a zonation method to differentiate the horizontal zones with different characteristics of spatial variabilities. Some uniaxial compressive strength and standard penetration test data are used to illustrate the proposed zonation method and the effect of zonation on the prediction accuracy. The results show that the proposed method is effective in distinguishing zones with different spatial variabilities and the improved zonation method facilitates more accurate predictions of unknown parametric values.